2008 4th International Conference on Emerging Technologies 2008
DOI: 10.1109/icet.2008.4777500
|View full text |Cite
|
Sign up to set email alerts
|

Seamless vertical handoff using Authentication Certificate in GPRS-WLAN tightly coupled integrated networks

Abstract: Authentication is a key requirement in security of integrated wireless networks. A Mobile Node (MN) requires to be re-authenticated whenever it performs vertical handoff in integrated wireless networks. The re-authentication causes delay in communication. If MN is not re-authenticated, it causes an even more serious problem of unauthorized entry in a network. In order to solve this problem, we have proposed a scheme for seamless vertical handoff. In proposed scheme, MN performs first authentication and gets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In [15], Yu Zhou et al proposed a dual-mode mobile terminal module for the integrated UMTS-WLAN network and suggested an algorithm based on network access selection. [16], for a tightly coupled GRPS-WLAN network the authors suggested an authentication scheme of a mobile node in a heterogeneous wireless during the vertical handover. M. Shi et.al [17], develop an agent based scheme for a WLAN-cellular network.…”
Section: Related Workmentioning
confidence: 99%
“…In [15], Yu Zhou et al proposed a dual-mode mobile terminal module for the integrated UMTS-WLAN network and suggested an algorithm based on network access selection. [16], for a tightly coupled GRPS-WLAN network the authors suggested an authentication scheme of a mobile node in a heterogeneous wireless during the vertical handover. M. Shi et.al [17], develop an agent based scheme for a WLAN-cellular network.…”
Section: Related Workmentioning
confidence: 99%